Very volatile organic compounds: an understudied class of indoor air pollutants. (24th December 2014) - Salthammer, T.
Abstract: Very volatile organic compounds (VVOCs), as categorized by the WHO, are an important subgroup of indoor pollutants and cover a wide spectrum of chemical substances. Some VVOCs are components of products commonly used indoors, some result from chemical reactions and some are reactive precursors of secondary products. Nevertheless, there is still no clear and internationally accepted definition of VVOCs. Current approaches are based on the boiling point, and the saturation vapor pressure or refer to analytical procedures. A significant problem is that many airborne VVOCs cannot be routinely analyzed by the usually applied technique of sampling on Tenax TA ® followed by thermal desorption GC/MS or by DNPH‐sampling/HPLC/UV. Some VVOCs are therefore often neglected in indoor‐related studies. However, VVOCs are of high significance for indoor air quality assessment and there is need for their broader consideration in measurement campaigns and material emission testing.